Odpowiedzi

2010-02-11T19:40:24+01:00
Zad . 6
a) 9+x=1 * 7/8 | * 8
72 + 8x = 8 * 7
72 + 8x = 56
8x = 56 - 72
8x = - 16 | : 8
x = - 2
d) 6 * 1/8y = 1 | * 8
48 * y = 8
y = 8 - 48
y = 40
g) 8a + 4 = 36
8a = 36 - 4
8a = 32 | : 8
a = 4
j) -3/4 - 1/4l = 2,25 | * 4
- 3 - l = 9
- l = 9 + 3
-l = 12 | * -1
l = - 12
zad . 7
a) 2*(x-1/2)- x + 3 = 3
2x - 1 - x + 3 = 3
x + 2 = 3
x = 1
b) 0 = 3-(2x+1)
-6x - 3 = 0
- 6x = 0 + 3
- 6x = 3 | : - 6
x = - 1/2
spr . A :
2(x-1/2)-x+3=3
2(1-1/2)-1 + 3 = 3
2 - 1 - 1 + 3 = 3
0 + 3 = 3
3=3
spr . B :
0 = 3-(2x+1)
3-(2*-1/2+1)=0
-1+1=0
0=0
1 5 1
Najlepsza Odpowiedź!
2010-02-11T19:50:06+01:00
Zad 6
a)
9+x=1 7/8
9+x=15/8 /*8
72+8x=15 /-72
8x= -57 /:8
x= -7 1/8

d)
6 1/8y= 1
49/8y=1 /*8
49y=8 /:49
y= 8/49

g)
8a+4=36 /-4
8a=32 /:8
a= 4

j)
-3/4 - 1/4l=2 1/4
-3/4 - 1/4l =5/4 /*4
-3 -l=5 /+3
-l=8 /:(-1)
l=-8

zad 7
a) 2(x-1/2) - x+3 =3
2x-1-x+3=3
x+2=3 /-2
x=1

b) 0=3-(2x+1)
0=3(-2x-1)
0=-6x-3 /+3
3=-6x
-6x=3 /:(-6)
x=-3/6
x=-1/2
1 4 1